Evaluation of the Application of Electronic Medical Records with a Technology Acceptance Model Approach in Hospital X - Himawan, Anzhela (Eduvest - Journal of Universal Studies, 2025)
This study evaluates the implementation of Electronic Medical Records (EMR) at Hospital X using the Technology Acceptance Model (TAM) to understand the factors influencing medical staff's acceptance and use of the system. The objective of this research is to analyze the use of EMR at Hospital X, focusing on how healthcare professionals and administrative staff utilize this technology in their work. The study aims to assess the effectiveness of EMR implementation, identify factors affecting EMR usage, and determine the extent to which the technology supports work efficiency and healthcare services. Additionally, the study seeks to provide strategic recommendations for hospital management to enhance EMR utilization, address existing challenges, and ensure the technology positively impacts individual and organizational performance overall. Data collection was conducted using questionnaires, and data analysis was performed with Partial Least Squares - Structural Equation Modeling (PLS-SEM). Data were gathered through an online survey and analyzed using SmartPLS 4 software. The analysis results indicate that Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) significantly influence user attitudes and intentions. Although EMRs can improve efficiency and reduce medical errors, challenges such as user resistance and system integration issues persist. This study highlights the importance of enhancing ease of use and perceived benefits, as well as creating a positive user experience to boost technology adoption. The findings provide insights into effective strategies for adopting new technologies and improving the success of EMR implementation in the healthcare sector.